2011
DOI: 10.5812/kowsar.1735143x.4203
|View full text |Cite
|
Sign up to set email alerts
|

Effect and Predictive Elements for 52 Weeks’ Telbivudine Treatment on Naïve HBeAg positive Chronic Hepatitis B

Abstract: BackgroundAntiviral treatment with nucleoside analogs has been used for chronic hepatitis B (CHB). Each kind of nucleoside analog has its own characteristics and suitability for patients. Telbivudine (LdT, brand name: Sebivo, Beijing Novartis Pharma Ltd) is the newest nucleoside analog, with strong and rapid viral suppression. However, its resistance rate is relatively high during long-term application, due to low genetic barriers to resistance. So, it is necessary to increase the effect and reduce resistance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…In this study, we longitudinally investigated the therapeutic effect and immunomodulatory function of LDT in CHB patients. We found that treatment with LDT significantly reduced the levels of serum HBV DNA, ALT, and AST, demonstrating that treatment with LDT inhibited HBV DNA replication and improved liver function in CHB patients, consistent with a previous report (31). In addition, treatment with LDT did not cause obvious side effects in the CHB patients tested.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, we longitudinally investigated the therapeutic effect and immunomodulatory function of LDT in CHB patients. We found that treatment with LDT significantly reduced the levels of serum HBV DNA, ALT, and AST, demonstrating that treatment with LDT inhibited HBV DNA replication and improved liver function in CHB patients, consistent with a previous report (31). In addition, treatment with LDT did not cause obvious side effects in the CHB patients tested.…”
Section: Discussionsupporting
confidence: 91%
“…Our real-world data validated the importance of baseline characteristics and on-treatment virologic responses at week 24 of therapy for the clinical outcomes of LdT-treated CHB patients. Higher baseline serum ALT and lower serum HBV-DNA levels were correlated with improved therapeutic responses to LdT treatment [25,26]. A serum HBV-DNA level less than 1000 copies/mL at week 12 was observed to be a more accurate predictor of viral suppression at year 2 of LdT treatment [27].…”
Section: Dynamics Of Qhbsag During Ldt Treatmentmentioning
confidence: 99%